Meridional variations of Sea Surface Temperature and Wind over Southern Sea of Java and Its Surroundings - Iis Sofiati; Erma Yulihastin; Suaydhi Suaydhi; Muhammad Fadhlan Putranto (Diponegoro University Semarang Indonesia, 2020)
Sea surface temperature (SST) plays an important role in controlling the ocean’s heat content and regulating climate. The seasonal characteristics of SST and wind speed and their correlation in the southern Java are investigated using satellite observations. The method use in this study is averaging hourly into monthly data for SST and wind speed during 20 years observation for period of 2000-2019, and representing it in the form of descriptive monthly and seasonally. The detailed correlation research was focused on the (0-5)°S, (5-10)°S, and (10-15)°S. The results show that SST reached its peak in August, while wind speed reached its minimum in August. The difference in SST (wind speed) for climatological condition lower (higher) in MJJASO, and the magnitude is more fluctuating in latitude average rather than in NDJFMA. The significant results of the study describe meridional variation in SST and wind between the northern (Karimata Strait), central (Java Sea), and southern (Indian Ocean) regions. In this case, the Indian Ocean region near south of Java has the highest correlation between SST and wind for both of dry and rainy season compared to other areas.